Examining the Tensions between Rapport with Pre-Service Teachers and Authority in Becoming a Teacher Educator. Issue 3 (1st September 2020) - Phillips, Andrea; Park Rogers, Meredith
ABSTRACT: The purpose of this self-study was to examine an internal conflict the lead author was feeling about her credibility to teach pre-service elementary teachers when she was similar in age to them and had no K-12 teaching experience. Having taught only as an undergraduate science teaching assistant, she was now assigned in her doctoral program to be an early field experience instructor for elementary education majors. Using Relational Cultural Theory and the framework of deliberate relationship, the role of rapport was analyzed in relation to authority and credibility. Findings show the lead author's rapport with her pre-service teachers was valuable in supporting her authority and credibility as an instructor, but only when boundaries to rapport were maintained. Specifically, findings show the difficulty in balancing caring for pre-service teachers with appropriate boundaries, and need for diligent transparency of practice. Implications for successful teacher-student relationships when feeling tensions between developing rapport and authority are discussed. Positive, mutually-beneficial relationships with high rapport are possible as long as the instructor maintains appropriate boundaries with pre-service teachers by focusing on the teacher-student relationship rather than attempting to establish friendships.